PENERAPAN TEKNIK COGNITIVE RESTRUCTURING UNTUK MENGURANGI GEJALA DISSOCIATIVE TRANCE DISORDER SISWA SMAN 1 KADEMANGAN - Umi Hidayatin (Center of Language and Cultural Studies, 2017)
This study described Cognitive Restructuring (CR) to reduce simthompts of Dissociate Trance Disorder (DTD) in the rehearsals process on athletic activities and how CR increased cognitive process to reasoning, understanding and reducing DTD. This study used classroom action research design with two cycles. The study was conducted in SMAN 1 Kademangan, Blitar. The study revealed that CR improved students skills to reduce DTD that raised internally through physical activities or mentally through thinking process.